Pembuatan Pupuk Kompos Dari Kotoran Kambing - Enni Halimatussa’diyah; Desi Nurlita; Miranda Salsabilla Fahendra (Jurnal Dirosah Islamiyah, 2023)
Organic fertilizers are fertilizers derived from various natural fertilizer-making materials such as animal manure, animal body parts, plants, which are rich in minerals and good for the use of soil enrichment. The purpose of writing this journalistofind out how to make compost from goat manure. The research method used is library research by collecting various information from journals, books and others. The results showed that the manufacture of organic fertilizer from goat manure has always been a product that is often used by farmers, because it has nutrients, rich minerals for plant fertilizer and growth and is safe for the health of farmers, because it is free from harmful chemicals. Keywords: Compost, Goat Manure.